PENGARUH KOMPENSASI, BEBAN KERJA DAN PERSEPSI JENJANG KARIR DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI TERHADAP LOYALITAS PERAWAT (STUDI PADA RUMAH SAKIT SWASTA TIPE D DI KABUPATEN BANYUMAS) - Khusnul KA. Nurcahyanti; Dyah Retno Kuswandani (ITB AAS INDONESIA Surakarta, 2021)
Loyalty is a person’s attitude to maintain his job and do the job with maximum. Loyalty level’s can be seen from the turnover, some things that become loyalty factoris job satisfaction, compensation, work load, and career ladder perception. This study aims to determine statistically the influence of variable compensation, workload and perception with job satisfaction as a mediator of nurse loyalty in Type D Private Hospital in Banyumas Regency. The research sampling method using propotional random sampling amounted to 40 nurses. Data collection techniques by survey by distributing questionnaires. The method of analysis used is regression analysis. From the results of this study can be concluded that job satisfaction, compensation, and career ladder perception have an effect on nurse loyalty, work load does not have an effect on loyalty, compensation and perception of career ladder influence to job satisfaction and work load does not have an effect on to nurse job satisfaction. Keywords : compensation, workload, perception of career, satisfactio